EFFECT OF CRYOGENIC AND NATURAL AGING PROCESS APPLIED TO Al-Zn-Mg-Cu ALLOYS ON LIFE TIME CALCULATION: Received: 19th June 2023; Revised: 29th June 2023, 12th October 2023, 25th October 2023; Accepted: 31st October 2023 - Altuntaş, Gözde; Altuntaş, Onur; Bostan, Bülent (MATTER: International Journal of Science and Technology, 2023)
In this study, life time calculation of aluminum 7075 alloy with cryogenic and natural aging processes was performed by thermal analysis. The aluminum alloy was quenched after solid solution treatment at 480°C and naturally aged for 10-100 days at room temperature (25°C). Other samples were cryogenically treated at -40°C and -80°C for 2 hours after solid solution treatment at 480°C. After the cryogenic treatment, natural aging was done at room temperature for 10-100 days. At the end of each period determined for the samples, the hardness values were measured. It was observed that there was no significant change in hardness values at the end of 10 and 100 days at -80 °C. Thus, it was determined that the natural aging process does not start after cryogenic treatment at -80 °C. It was observed that the hardness value of naturally aged samples after cryogenic treatment at -40 °C increased more than the natural aged samples only. This showed that -40 °C improved the mechanism by creating a driving force in the material. Life time calculations between 30 °C and 320 °C also showed that -40 °C cryogenic treatment + natural aging increased life time by approximately 20% compared to natural aging alone.